2007
DOI: 10.1074/jbc.m701658200
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADAM-9 Disintegrin-Cysteine-rich Domains in Human Keratinocyte Migration

Abstract: ADAM-9 belongs to a family of transmembrane, disintegrincontaining metalloproteinases involved in protein ectodomain shedding and cell-cell and cell-matrix interactions. The aim of this study was to analyze the expression of ADAM-9 in skin and to assess the role of this proteolytic/adhesive protein in skin physiology. In normal skin, ADAM-9 expression was detected in both the epidermis and dermis and in vitro in keratinocytes and fibroblasts. Here we report that ADAM-9 functions as a cell adhesion molecule via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 41 publications
0
58
0
Order By: Relevance
“…Further evidence of the adhesive function of cysteine has been found in many cell adhesion proteins, since they can promote cell adhesion through their cysteine-rich domains. [19][20][21][22][23] Cysteine is assumed to play a role in maintaining the topology of charged amino acids on the molecular surface by the formation of intramolecular disulfidebonds.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of the adhesive function of cysteine has been found in many cell adhesion proteins, since they can promote cell adhesion through their cysteine-rich domains. [19][20][21][22][23] Cysteine is assumed to play a role in maintaining the topology of charged amino acids on the molecular surface by the formation of intramolecular disulfidebonds.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were resuspended in HEPES buffer (1 mM Hepes, 0.5% BSA, 1 mM of each CaCl 2 and MnCl 2 ). Adhesion assays were performed as described before (10). Briefly, 96-well tissue culture plates were coated with recombinant DC-9 and His 6 peptide (0.6 M) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that ADAM-9 is expressed in both human and mouse epidermis. In keratinocytes, the adhesive activity of ADAM-9 leads to modulation of MMP-9 expression and cell migration (10). Further, proteolysis via ADAM-9 in keratinocytes has been shown to be important for the constitutive shedding of collagen XVII (11).…”
mentioning
confidence: 99%
“…Although studies have often focused on the proteolytic activity of members of this family, there is increasing evidence that they play a role in cell adhesion through direct interaction with integrins. ADAM9 is a widely expressed non-Arg-Gly-Asp-containing molecule, which has been shown to bind to αvβ5 on myeloma cells, α3β1 on keratinocytes, and α6β1 on fibroblasts (28,29,(31)(32)(33)(34). These studies raise the possibility that ADAM9 could mediate cell-platelet interactions to regulate dissemination of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant DC-9 was produced as previously described (33). Briefly, HEK293-EBNA cells were transfected by JetPei (Polyplus) with pCEP-pu BM40-cHis-Dis-Cys plasmid giving rise to a fusion protein with a His6 tag placed in frame with disintegrin-cysteine-rich coding regions of ADAM9.…”
Section: Methodsmentioning
confidence: 99%